Disc Regeneration Using MSC Transplanted via the Endplate Route. Issue 1 (April 2016) - Vadalà, Gianluca; Russo, Fabrizio; Musumeci, Maria; Valentini, Alessia; Bernardini, Marco; Denaro, Luca; D'Avella, Domenico; Giordano, Rosaria; Denaro, Vincenzo
Introduction: Stem cell based intervertebral disc (IVD) regeneration is quickly moving toward clinical applications. 1 However, many aspects need to be investigated to routinely translate this therapy to clinical applications, in particular, the most efficient way to deliver cell to the IVD. Cells are commonly delivered to the IVD through the annulus fibrosus (AF) injection. However, recent studies have shown serious drawbacks of this approach 2–4 suggesting that intradiscal injection through the AF route itself is not completely innocuous and may disable the treatments to therapeutic agents delivered. As an alternative we have described and tested a new surgical approach to the IVD via the endplate-pedicles (transpedicular approach). The Purpose of the study was to test MSCs/hydrogel transplantation for IVD regeneration in a grade IV preclinical model of IDD on large size animals via the transpeducular approach 5 with cell dose escalation. Material and Methods: Adult sheep ( n = 18) underwent bone marrow aspiration for autologous MSC isolation and expansion. MSC were suspended in autologous PRP and conjugated with Hyaluronic Acid and Batroxobin at the time of transplant (MSCs/hydrogel). Nucleotomy was performed via the transpedicular approach under fluoroscopy 6 in four lumbar IVDs and that were injected with 1) hydrogel, 2) Low doses of MSC/hydrogel [5x10 6 cell/ml] 3) High doses of MSC/hydrogel [1x10 7 cell/ml], 4) no injection (CTRL). The endplate tunnel was sealed using a polyurethane scaffold. 7 X-ray and MRI were performed at baseline and 1, 3, 6, 12 months. Disc height and MRI indexes were calculated at each time point. Disc macro- and micro-morphology were analyzed at each time point. Results: The MRI index showed a significant decrease in the untreated group, the disc injected with hydrogel and those injected with low MSC dose compared with healthy discs in all time points. The discs treated with high dose of MSC showed maintenance of the MRI index compared with the healthy disc. Morphologically, the grade of degeneration evaluated using the Thompson grade system 8 was in agreement with the grades observed at the MRI. The High MSC dose treated discs demonstrated abundant cartilage formation at 3 months, and to a lesser extent at 6 and 12 months. For the carrier and low MSC dose treated groups, however, there was less proteoglycan matrix. Conclusion: An effective dose of autologous MSC [1x10 7 cell/ml] delivered via the alternative transpedicular approach regenerates the NP in a preclinical model of grade IV IDD. These data highlight as the disc regeneration can be achieved maintaining the AF intact via the end-plate route. This preclinical study has high translational value as large animal model with the long fallow up were used, MSCs were expanded in GMP facility simulating the clinical scenario, and the hydrogel were composed of clinically available drags and materials. This study bring a significant contribution toward the translation of regenerative therapies for the biological restoration of degenerative changes in the IVD, which is crucial to improve present clinical treatment and life quality of several patients. Acknowledgment: The support of the Italian Ministry of Instruction, University and Research Grant (PRIN-200938NT8Z), the Young Investigator Research Grant of the Italian Ministry of Health (GR-2010–2318448) and the BIOSPINA Award of the Italian Society of Spine Surgery (SICV&GIS) are gratefully acknowledged. References Orozco L, Soler R, Morera C, Alberca M, Sánchez A, García-Sancho J. Intervertebral disc repair by autologous mesenchymal bone marrow cells: a pilot study. Transplantation 2011;92(7):822–828 Carragee EJ, Don AS, Hurwitz EL, Cuellar JM, Carrino JA, Herzog R. 2009 ISSLS Prize Winner: Does discography cause accelerated progression of degeneration changes in the lumbar disc: a ten-year matched cohort study. Spine 2009;34(21):2338–2345 Korecki CL, Costi JJ, Iatridis JC. Needle puncture injury affects intervertebral disc mechanics and biology in an organ culture model. Spine 2008;33(3):235–241 Vadalà G, Sowa G, Hubert M, Gilbertson LG, Denaro V, Kang JD. Mesenchymal stem cells injection in degenerated intervertebral disc: cell leakage may induce osteophyte formation. J Tissue Eng Regen Med 2012;6(5):348–355 Vadalà G, Russo F, Pattappa G, et al. The transpedicular approach as an alternative route for intervertebral disc regeneration. Spine 2013;38(6):E319–E324 Vadalà G, De Strobel F, Bernardini M, Denaro L, D'Avella D, Denaro V. The transpedicular approach for the study of intervertebral disc regeneration strategies: in vivo characterization. Eur Spine J 2013;22(Suppl 6):S972–S978 Vadala G, et al. A nucleotomy model with intact annulus fibrosus to test intervertebral disc regeneration strategies. Tissue Eng Part C Methods 2015;21(11):1117–1124 Thompson JP, Pearce RH, Schechter MT, Adams ME, Tsang IK, Bishop PB. Preliminary evaluation of a scheme for grading the gross morphology of the human intervertebral disc. Spine 1990;15(5):411–415